CO line emission in the halo of a radio galaxy at z = 2.6 - Nesvadba, N.; Neri, R.; De Breuck, C.; Lehnert, M.; Dowries, D.; Walter, F.; Omont, A.; Boulanger, F.; Seymour, Nick (Wiley-Blackwell Publishing Ltd., 2009)
We report the detection of luminous CO(3-2) line emission in the halo of the z = 2.6 radio galaxy (HzRG) TXS0828+193, which has no detected counterpart at optical to mid-infrared wavelengths implying a stellar mass ? few × 109 M and relatively low star formation rates. With the IRAM Plateau de Bure Interferometer (PdBI), we find two CO emission-line components at the same position at ~80 kpc distance from the HzRG along the axis of the radio jet, with different blueshifts of few 100 km s-1 relative to the HzRG and a total luminosity of ~2 × 1010 K km s-1 pc2 detected at a total significance of ~8s HzRGs have significant galaxy overdensities and extended haloes of metal-enriched gas often with embedded clouds or filaments of denser material, and likely trace very massive dark matter haloes. The CO emission may be associated with a gas-rich, low-mass satellite galaxy with very little ongoing star formation, in contrast to all previous CO detections of galaxies at similar redshifts. Alternatively, the CO may be related to a gas cloud or filament and perhaps jet-induced gas cooling in the outer halo, somewhat in analogy with extended CO emission found in low-redshift galaxy clusters. © 2009 The Authors. Journal compilation © 2009 RAS.